Analysis of the Correlation between Academic Staff in Universities in Constanța and the Average Monthly Labor Cost in Tertiary Education - Cosmina-Gabriela Nitu (Figher); Mihaela Neculita (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
This paper aims to highlight the relationship between the number of individuals working as academic personal in higher education in Constanța County and the average monthly employment cost per employee in the educational system over a twelve-year period. Using the database published online by the National Institute of Statistics, it will be concluded whether there is a dependency relationship between the two variables, with the help of a simple linear regression statistical-econometric model.